Development of Ecotourism Based on Mangrove Conservation To Deal With Coastal Abrasion: Potential And Challenges In Cirebon - Setiawan, Agung (Ann Publisher, 2025)
Background. The problem of coastal abrasion has become a serious threat to coastal areas in various regions in Indonesia, including Cirebon. Coastal abrasion, which is the erosion of coastlines caused by ocean waves, currents, and human activities, results in a reduction of land area and damages coastal ecosystems. Aims. This research aims to address the issue of abrasion in the coastal area of Cirebon Regency by developing an ecotourism model centered on mangrove conservation. Methods. The research methods used include field surveys, geospatial data analysis, and community involvement in the ecosystem rehabilitation process. Result. The study's results show that rehabilitating mangroves covering an area of 10 hectares can reduce abrasion by up to 50%, while developing mangrove educational tourism routes can increase community income by up to 20%. Additionally, there has been a notable increase in public awareness of the importance of environmental conservation. Conclusion. The contribution of this research includes the development of sustainable ecotourism models that not only support ecosystem conservation but also empower local economies. Implementation. Integrating mangrove ecotourism development programs into regional development plans and providing incentives to the community and the private sector involved in the rehabilitation and management of mangrove areas